The influence of textile finishing agents on the biodegradability of shed fibres. Issue 14 (6th July 2021) - Lykaki, Marianna; Zhang, Ya-Qi; Markiewicz, Marta; Brandt, Stefan; Kolbe, Sabrina; Schrick, Jörg; Rabe, Maike; Stolte, Stefan
Abstract : Biodegradation of shed fibres originated from textile washing. Abstract : Multiple studies on textiles have shown that significant numbers of microparticulate fibres are released daily during washing and are discharged to sewer and wastewater treatment plants (WWTPs). These fibres can enter the environment and potentially cause adverse impacts on ecosystems. The aim of the present study is to evaluate the biodegradability (mineralization) of microplastic fibres compared to natural (cellulose), regenerated (viscose), polyethylene terephthalate (PET)/cotton blend and oxo-degradable PET fibres under laboratory conditions using a 60-day ready biodegradability test and an inoculum from a WWTP. Moreover, the influence of different textile finishes on the biodegradability of fibres was investigated using viscose fibres treated with two different types of reactive dyes (two- and three-anchor compounds), a cationic silicone based softener and a cationic quaternary amonium compound based antimicrobial agent. High mineralization of cotton as well as viscose was observed (reaching 70%), while PET fibres were not degraded (approx. 1.6%). Viscose fibres impregnated with certain finishing agents exhibited a lower degradation level (around 75%) than untreated fibres (reaching up to 85%), which indicates that textile finishing might also prolong the environmental half-lives of shed fibres. The addition of softener to the dyed fibres affected slightly their biodegradability, while the addition of antimicrobial agent significantly reduced the biodegradation level to 3–5%. The recalcitrance of treated fibres against biodegradation might be dependent on the durability and type of the finish. This is an important fact when aiming and chemically designing for more sustainable textile products.